Altered fibrin clot properties in advanced lung cancer: impact of chemotherapy - Królczyk, Grzegorz; Ząbczyk, Michał; Czyżewicz, Grzegorz; Plens, Krzysztof; Prior, Shannon; Butenas, Saulius; Undas, Anetta (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: Faster formation of dense and poorly lyzable fibrin networks have been reported in patients at risk of thromboembolism, including cancer patients. We sought to investigate whether chemotherapy affects plasma fibrin clot properties and their determinants in lung cancer patients. Methods: In this observational study we enrolled 83 consecutive patients with advanced inoperable lung cancer. Plasma fibrin clot permeability (Ks), turbidimetric analysis of clot formation, clot lysis time (CLT), microparticle-associated tissue factor (MP-TF) activity, and thrombin generation parameters were investigated at enrolment and 3–4 months after standard chemotherapy. Results: Lung cancer patients after 4 (range, 4–5) cycles of chemotherapy had 35.6% higher D-dimer, 22.1% lower MP-TF activity, and unaltered fibrinogen compared with baseline. Chemotherapy resulted also in 7.5% increased Ks, 8.6% prolonged lag phase, and 5.4% shortened CLT, while thrombin generation was unchanged. Chemotherapy-related differences in clot structure were confirmed by scanning electron microscopy images. Fibrin clot properties after chemotherapy did not differ among histological types of lung cancer, cancer stages or chemotherapy regimens. Interestingly, never smoking (n=13, 16%) was associated with looser post-treatment fibrin structure as reflected by 12.3% higher Ks. Multiple linear regression showed that more advanced cancer stage, higher peak thrombin generation, and higher white blood cell count determined post-treatment change in Ks, while active smoking was associated with change in CLT. Conclusions: Three-month chemotherapy in lung cancer patients improves clot properties despite unaffected thrombin generation, suggesting that anticancer treatment might quickly produce antithrombotic actions.